2021
DOI: 10.3390/su13031287
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sustainable Thinking by Information Literacy

Abstract: Developing the sustainable thinking of students is an important preoccupation of specialists, teachers, and civil society. Information literacy represents the development of students’ skills to search, identify, evaluate, and ethically use scientific information. Is there a connection between sustainable thinking (ST) and information literacy (IL)? Through a scientometric study in the Web of Science (WOS) database, the authors identify clusters of keywords, analyze the articles identified in WOS, and identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In the perspective of the conclusions mentioned above, it is possible to say that information literacy in general, but especially the green IL, can be seen as a key to the economic, social, and cultural development of communities, institutions, and even nations. Repanovici et al [53] showed through their scientometric study of the literature, and a qualitative research study, i.e., a survey, that the nearest efforts towards transforming society into a sustainably developing one should focus on educators and building their own understanding of the whole concept. The authors also demonstrated that IL influences and reinforces the ability to think in sustainability categories, and brings forth sustainable behaviors among the public.…”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the perspective of the conclusions mentioned above, it is possible to say that information literacy in general, but especially the green IL, can be seen as a key to the economic, social, and cultural development of communities, institutions, and even nations. Repanovici et al [53] showed through their scientometric study of the literature, and a qualitative research study, i.e., a survey, that the nearest efforts towards transforming society into a sustainably developing one should focus on educators and building their own understanding of the whole concept. The authors also demonstrated that IL influences and reinforces the ability to think in sustainability categories, and brings forth sustainable behaviors among the public.…”
Section: Educationmentioning
confidence: 99%
“…The authors also demonstrated that IL influences and reinforces the ability to think in sustainability categories, and brings forth sustainable behaviors among the public. Finally, they suggest launching a module within the IL courses that would be devoted to informing students about the connection between the way they use their information and research skills, and the generation of carbon footprint by the information technology equipment [53]. Repanovici et al also claim that the sustainable IL is situated at the intersection of three core elements of a higher education system, namely research, curricula, and library.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…But what is green growth? There is a developed literature that defines the concept of green growth (Hallegatte & al., 2012;Smulders & al., 2014;Stoknes & Rockström, 2018) but also the concept associated with it, the green economy (Loiseau & al., 2016;Georgeson & al., 2017, Kasztelan, 2017 or various green activities or areas (Repanovici at. Al 2021;Polonsky & Rosenberger, 2001;Hsiao & at., 2018).…”
Section: Green Growth In Briefmentioning
confidence: 99%
“…Environmental education is among the important education for achieving sustainable development (Biplap & Rajidulhoque, 2015;Karpan et al, 2020;Shutaleva et al, 2020). The Ministry of Education Malaysia has taken steps to integrate environmental education into the curriculum in schools; one of them is through the Moral Education curriculum (Haliza, 2017).…”
Section: Introductionmentioning
confidence: 99%